The hidden secrets of the Yin-Yang symbol - Xin Li (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2014)
(1) The essence of Yin-Yang is that yin and yang are contrary yet complementary. 阴阳的本质是阴阳是相生相克的关系。 (2) This contrary yet complementary relationship can be described by three characteristics of Yin-Yang: nonexclusivability, transformability, and coopetitionability. Nonexclusivability means that anything contains yin and yang elements and neither yin nor yang elements can be excluded because within both elements there is a seed of the opposite element. Due to the existence of a seed of the opposite element, the yin and yang elements can be mutually transformed when the opposite seed grow to a certain size. Due to this possible growth of the inside opposite element, the relationship between yin and yang and their inside opposite element is one of competition and cooperation, i.e. coopetition. When the configuration ratio of an element's opposite seed is within the range of 1% to 25%1, their relationship is more co-operative than competitive, and therefore there is more synergy than tradeoff between them. The closer the ratio is to 25%, the stronger the synergy. When the ratio is within the range of 25% to 49%, their relationship is more competitive than cooperative, and therefore there is more tradeoff than synergy between them. The closer the ratio is to 49%, the stronger the tradeoff. 阴阳的相生相克关系可以描述为三个特性：不可排除性、相互转化性、竞 争合作性。不可排除性是指任何事物都包含阴阳两个对立元素，二者之任 何一个均不可能被排除在我，这是因为在阴或阳元素内部天然的包含着对 立元素的种子。正是因为这个种子的天然存在，阴和阳元素可以互相转 化，这种转化发生在对立元素种子成长到一定程度的时候。正是由于这种 对立元素的成长可能性，阴或阳元素和它内部的对立元素之间的关系是既 竞争又合作的。当内部的对立元素占总体元素的力量比例在1%到25%之 间时，两者的关系是合作多于竞争，越靠近25%这个点，这种合作的协同 效果也强烈。当这个搭配比例处于25%到49%之间时，它们的关系将是 竞争多于合作，也就是他们更多互相排斥而非互相促进。当这个比例越靠 近49%，这种排斥效应越强烈。
hdl:10398/8891
Keywords: 330; Östliche Philosophie; China